2013
DOI: 10.1016/j.sjbs.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative, antimicrobial and cytotoxic effects of the phenolics of Leea indica leaf extract

Abstract: This study investigated the phytochemical, antioxidative, antimicrobial and cytotoxic effects of Leea indica leaf ethanol extract. Phytochemical values namely total phenolic and flavonoid contents, total antioxidant capacity, DPPH radical scavenging effect, FeCl3 reducing power, DMSO superoxide scavenging effect and Iron chelating effects were studied by established methods. Antibacterial, antifungal and cytotoxic effects were screened by disk diffusion technique, food poison technique and brine shrimp bioassa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 37 publications
0
54
2
Order By: Relevance
“…This result different with the previous study reported from Malaysia where the phenolic concentration of 19.15 mg GAE/g from the ethanolic extract, 15.61 mg GAE/g from ethyl acetate and 1.29 mg GAE/g from n-hexane extract (Reddy et al, 2012). Another study conducted in Bangladesh also reported differently (Rahman et al, 2012), indicating that there is a different in phenolic concentration in L. indica leaf. There are several factors affecting the phenolic compound of plant including the environmental condition such as climate, season, geographical condition, precipitation, temperature and land (Bouterfas et al, 2014).…”
Section: Concentration Of Total Phenolic and Flavonoidcontrasting
confidence: 85%
“…This result different with the previous study reported from Malaysia where the phenolic concentration of 19.15 mg GAE/g from the ethanolic extract, 15.61 mg GAE/g from ethyl acetate and 1.29 mg GAE/g from n-hexane extract (Reddy et al, 2012). Another study conducted in Bangladesh also reported differently (Rahman et al, 2012), indicating that there is a different in phenolic concentration in L. indica leaf. There are several factors affecting the phenolic compound of plant including the environmental condition such as climate, season, geographical condition, precipitation, temperature and land (Bouterfas et al, 2014).…”
Section: Concentration Of Total Phenolic and Flavonoidcontrasting
confidence: 85%
“…The induction of diarrhea by castor oil is attributed to its active ingredient ricinoleic acid which stimulates the production of several inflammatory mediator substances that include prostaglandins, nitric oxide, and platelet activating factor, cAMP, histamine and tachykinins [50]. The mediators thus released promote vasodilatation, smooth muscle contraction, and mucus secretion in the small intestines.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial plasminogen activator such asstaphylokinase, streptokinase, act as cofactor molecules that cause exosite formation and improve the substrate performance towards the enzyme. Staphylokinase activates plasminogen to be in a position to break down clots, also damages the extracellular matrix and fibrin particles that keep cell together (Parry et al, 2000;Collen, 1990;Rahman et al, 2013). From the above experiments, it would be alluring to investigate both the mechanism underlying clot lytic effects demonstrated by C. barbata and E. pursaetha leaf extract.…”
Section: Discussionmentioning
confidence: 99%